1986
DOI: 10.1029/ja091ia03p03089
|View full text |Cite
|
Sign up to set email alerts
|

SSC‐excited pulsations recorded near noon on GEOS 2 and on the ground (CDAW 6)

Abstract: The SSC occurring on March 22, 1979, at 0826 UT had an unusually sharp onset in Scandinavia, in Middle Europe and in experiments on the geostationary satellite GEOS 2, which was near noon, local magnetic time. The ground magnetometer stations showed a small preimpulse which started ∼5 s before the main impulse. Both impulses needed ∼2 s to “propagate” from ground stations at L = 6.3–4.6. Search coil magnetometers indicate a very small precursor in northern Finland (L ∼ 4.4–6.0) which started ∼15–20 s before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…This apparent propagation of the MI's is directed towards the equator in both the hemispheres. The similar effect of equatorward propagation of ssc onset at sub-auroral latitudes was reported by Wedeken et al (1986). It should be kept in mind that the observed time delays between peaks of the H components may correspond either to the equatorward propagation effect or to the increase of the rise time while approaching the equator.…”
Section: Experimental Databasesupporting
confidence: 49%
See 2 more Smart Citations
“…This apparent propagation of the MI's is directed towards the equator in both the hemispheres. The similar effect of equatorward propagation of ssc onset at sub-auroral latitudes was reported by Wedeken et al (1986). It should be kept in mind that the observed time delays between peaks of the H components may correspond either to the equatorward propagation effect or to the increase of the rise time while approaching the equator.…”
Section: Experimental Databasesupporting
confidence: 49%
“…Wedeken et al (1986) really revealed that the pre-impulse in the D component runs 5 sec ahead of MI, and is probably related to a burst of precipitating electrons. However, the observed pre-impulse of ssc had an amplitude much less than a typical PI.…”
Section: Possible Mechanisms Of MI and Pimentioning
confidence: 99%
See 1 more Smart Citation
“…They found that Psc 2.3's are generally observed at middle and low latitudes, while Psc 4's and Psc 5's are observed in the subauroral and auroral regions. Recently, Wedeken et al (1986) showed through a case study of an SSC with a number ofmagnetometers and the GEOS 2 satellite that the Psc had a complex spatial variation of spectral structure with a small value (m -0-4) of the azimuthal wavenumber, some features of which were consistent with the coupled global mode theory Southwood, 1985, 1986). Further, *Now at Ishikawajima System Technology Co., Ltd., Shinagawa-ku, Tokyo 141, Japan.…”
Section: Introductionmentioning
confidence: 57%
“…This surface impulse also can be coupled into the inner magnetosphere through the field line resonance mechanism, that was analyzed using simultaneous satellite observations of plasma drift velocity and magnetic field observations (cf. KOKUBUN, 1983;KUWASHIMA and FUKUNISHI, 1985;NAGANO and ARAKI, 1986;WEDEKEN et al, 1986).…”
Section: Sudden Impulse Caused By Interplanetary Shockmentioning
confidence: 99%